Normalized Curvature Ratio for Damage Detection in Beam-Like Structures - Kliewer, Kaitlyn; Glisic, Branko (Frontiers in Built Environment, 2017)
Fiber optic sensors (FOS) offer numerous advantages for structural health monitoring. In addition to being durable, lightweight, and capable of multiplexing, they offer the ability to monitor strain in both static and dynamic mode. FOS also allow for instrumentation of large areas of a structure with long-gauge sensors which helps enable global monitoring of the structure. Drawing upon these benefits, the Normalized Curvature Ratio (NCR), a curvature based damage detection method, has been developed. This method utilizes a series of long-gauge fiber Bragg grating (FBG) strain sensors for damage detection of a structure through dynamic strain measurements and curvature analysis. The main assumption is that the ratios between cross-sectional curvature amplitudes under free vibration remain unchanged given the state of the structure is unchanged. The theoretical development of this method is presented along with an analytical study of a simply supported beam with two damage cases: a loss of flexural stiffness in the span and a change in rotational stiffness of the support. Validation of the method is then performed through two implementations. First, through a small-scale laboratory test with a simply supported aluminum beam subjected to a change in the rotational stiffness of the support. Second, the method is applied to an existing in-service highway overpass with over 5 years of data collection of dynamic strain events. The advantages and limitations of the method are identified and discussed. This research shows encouraging results and the potential for the NCR to be used as a simplistic metric for damage detection.